2021
DOI: 10.1371/journal.pone.0260633
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of some epigenetic modifying drugs’ on Chlamydia pneumoniae-induced neuroinflammation: A novel model

Abstract: Chlamydia pneumoniae (Cpn) is a gram-negative intracellular pathogen that causes a variety of pulmonary diseases, and there is growing evidence that it may play a role in Alzheimer’s disease (AD) pathogenesis. Cpn can interact functionally with host histones, altering the host’s epigenetic regulatory system by introducing bacterial products into the host tissue and inducing a persistent inflammatory response. Because Cpn is difficult to propagate, isolate, and detect, a modified LPS-like neuroinflammation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 121 publications
1
3
0
Order By: Relevance
“…Our results corroborate, at least in part, with data from the literature. The neuroprotective effect of the RG108 inhibitor observed here can be correlated with a recent study that also reported its neuroprotective effect in a murine model of beta-amyloid (Aβ)-induced neurotoxicity [41]. On the other hand, studies report that SAMe, in a dose dependent manner, protects hippocampal CA1 neurons from degeneration and necrosis in rats subjected to transient and brief forebrain ischemia [42] in addition to induces antidepressant effects in preclinical and clinical studies of depression [43].…”
Section: Discussionsupporting
confidence: 84%
“…Our results corroborate, at least in part, with data from the literature. The neuroprotective effect of the RG108 inhibitor observed here can be correlated with a recent study that also reported its neuroprotective effect in a murine model of beta-amyloid (Aβ)-induced neurotoxicity [41]. On the other hand, studies report that SAMe, in a dose dependent manner, protects hippocampal CA1 neurons from degeneration and necrosis in rats subjected to transient and brief forebrain ischemia [42] in addition to induces antidepressant effects in preclinical and clinical studies of depression [43].…”
Section: Discussionsupporting
confidence: 84%
“…After 3 h, the medium was discarded, 100 μL of dimethyl sulfoxide (DMSO) was added to each well, and absorbance at 540 and 570 nm wavelengths were measured in a Cytation 3 multimode reader device (Biotek). The absorbance values obtained from the wells were correlated to the number of live cells, which was expressed as a percentage of the control group …”
Section: Methodsmentioning
confidence: 99%
“…The absorbance values obtained from the wells were correlated to the number of live cells, which was expressed as a percentage of the control group. 48 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation